Evaluation of rice allelopathy in hydroponics - Kim, S.Y.; Madrid, A.V.; Park, S.T.; Yang, S.J.; Olofsdotter, M. (Wiley, 2005)
The inhibitory activity of water extracts from the shoots and roots of three rice cultivars, Taichung native 1 (TN1) and IAC165 (both allelopathic rice) and AUS196 (non‐allelopathic rice), grown in hydroponics was evaluated. The release of germination inhibitors by allelopathic rice plants into hydroponic solution was also determined with freshly collected solution and XAD‐4 resin desorbate. The degree of the inhibition was quantified in terms of root growth in Echinochloa colona, Echinochloa crus‐galli, Echinochloa crus‐galli var. oryzicola, Triantema portulacastrum and Lactuca sativa. The allelopathic activity of rice was species specific, and depended on source and concentration. Root length of all test species was inhibited by the different concentrations of shoot extract of allelopathic and non‐allelopathic rice. However, of the three cultivars, TN1 showed higher inhibition than IAC165 and AUS196 in all test species. Water extracts of shoots and roots significantly inhibited root growth in E. crus‐galli but the shoot extract gave a greater inhibitory effect on E. crus‐galli than the root extract. Root exudate of TN1 inhibited root elongation of E. crus‐galli from 2 weeks after transplanting (WAT) and the inhibition continued for 4 WAT. The results confirmed the previous finding of a laboratory bioassay that the TN1 had allelopathic activity and produced allelochemicals that inhibit growth of some weed species.